Chlorine content analysis on white rice at the Pagesangan Market, Mataram City - Nurhidayatullah, Nurhidayatullah; Yuliansari, Dini; Fatmalia, Enida (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
In Indonesia, rice is a staple food consumed daily. The high purchasing power of the public for good quality rice makes this a reason for producers to add dangerous bleaching agents such as chlorine to improve the physical quality of the rice they sell. The use of unclear bleaching agents on rice that do not meet the requirements for permitted additives in food and whose concentrations exceed the threshold limits is dangerous for human health. This research aims to determine the presence of chlorine in white rice sold at the Pagesangan market. The methods used are qualitative and quantitative. Three of the five rice samples tested at the Mataram STTL Laboratory tested positive for chlorine. Chlorine levels in rice samples, sample C, were 367.4 mg/L, sample D was 275.1 mg/L, and sample E was 93.4 mg/L.